STRATEGI KEPALA SEKOLAH DALAM MEMPERTAHANKAN KUALITAS PENDIDIKAN PADA MASA COVID 19 - sahri sahri (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2022)
Schools are institutions that provide education that have devices and elements that are interrelated with each other. Schools that are expected by the community are those that are able to bring about changes that are designed to be responsive to the environment. Schools that win a competition in the future are schools that are able to respond to change. Changes and progress in educational institutions cannot be separated from the duties and obligations of the principal. So that the principal must be able to strengthen and improve and develop the quality and quantity of the school. The purpose of this article is to find out the various strategies carried out by school principals in maintaining and developing the quality of education in SMK AL Fattah. This type of research is descriptive qualitative research. The method used in data collection is observation, interviews and documentation. Meanwhile, in analyzing the data used there are several steps, namely by reducing data, presenting data and verifying. The results of the study indicate that there are several things that are done by the head of SMK AL Fattah Pungpungan in the quality and quality of education, namely first, planning input, process and output, secondly increasing teacher competence, thirdly improving facilities and infrastructure, fourthly improving students, fifth evaluation of activities School